2012
DOI: 10.1093/jopart/mus037
|View full text |Cite
|
Sign up to set email alerts
|

Internet, Trust in Government, and Citizen Compliance

Abstract: The decline of trust in government contributes to a climate of "political malaise," and leads to great challenges for any government concerned with meeting the public's demands and expectations. Starting from the premise that e-government and e-participation are desirable developments initiated by governments via a top-down approach, this paper explores the opportunities, if any, available to citizens to utilize the internet to initiate bottom-up channels of participation and communication. We explore the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 49 publications
4
142
0
Order By: Relevance
“…Internet use seems even damaging. Norris (2011) finds that it is associated with lower democratic satisfaction, while Im et al (2014) attest that citizens who spend more time on the web display a lower degree of trust in government, even though this negative effect is moderated by access to governmental websites.…”
Section: News Websites Social Media and Democracymentioning
confidence: 99%
“…Internet use seems even damaging. Norris (2011) finds that it is associated with lower democratic satisfaction, while Im et al (2014) attest that citizens who spend more time on the web display a lower degree of trust in government, even though this negative effect is moderated by access to governmental websites.…”
Section: News Websites Social Media and Democracymentioning
confidence: 99%
“…Following Putnam's (1995) widely discussed analysis of the corrosive effect of television, studies have reported on the decrease in social capital and political trust that may be fostered by different types of media technology (e.g. Im et al, 2014;Calenda and Meijer, 2009). In other research on the negative effects of the Internet, answers have suggested that the Internet may make citizens more cynical of government, especially in less democratically successful countries (Bailard, 2014;Hibbing & Theiss-Morse, 2002), or that the internet consolidates the political dominance of class elites, thus excluding others from avenues of civic engagement (Schlozman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Korea analysed the implications of Internet usage on trust in government [14]. Im et al draw a negative relation from internet usage in general towards trust in government, but they also argue that the usage of e-government could "reduce the negative impact of the Internet on trust in government" [14, p.16].…”
Section: Trust and E-participationmentioning
confidence: 99%
“…However, design principles guiding the development of trustworthy e-participation tools are not studied. x Im et al [14] x (x) Kim & Lee [15] x Uslaner & Brown [41] x (x) Wang et al [42] x…”
Section: Trust and E-participationmentioning
confidence: 99%
See 1 more Smart Citation